Agile Software Development Best Practices for Large Software Development Projects - Stober, Thomas; Hansmann, Uwe.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Software Development is moving towards a more agile and more flexible approach. It turns out that the traditional "waterfall" model is not supportive in an environment where technical, financial and strategic constraints are changing almost every day. But what is agility? What are today$1 (Bs major approaches? And especially: What is the impact of agile development principles on the development teams, on project management and on software architects? How can large enterprises become more agile and improve their business processes, which have been existing since many, many years? What are the limitations of Agility? And what is the right balance between reliable structures and flexibility? This book will give answers to these questions. A strong emphasis will be on real life project examples, which describe how development teams have moved from a waterfall model towards an Agile Software Development approach.s
The Flaw in the Plan -- Traditional Software Development -- Overview of Agile Software Development -- Tooling -- Considerations on Teaming and Leadership -- Considerations on Planning and Architecture -- Considerations on Project Execution -- Mix and Match -- Summary and Wrap-Up.
Keywords: Computer science; Data transmission systems; Computer Communication Networks; Software engineering; Information systems; Physics; Engineering; Computer Science; Software Engineering; Computer Communication Networks; Input/Output and Data Communications; Information Systems Applications (incl.Internet).; Complexity